An Efficient and Footprint-Free Protocol for the Transdifferentiation of Hepatocytes Into Insulin-Producing Cells With IVT mRNAs - Ma, Shinan; Yang, Mengjie; Zhou, Wenhui; Dai, Longjun; Ding, Yan; Guo, Xingrong; Yuan, Yahong; Tang, Junming; Li, Dongsheng; Wang, Xiaoli (Frontiers in Genetics, 2020)
Direct transdifferentiation of adult somatic cells into insulin-producing cells is a promising approach for cell-based therapies for type 1 diabetes mellitus (T1D). Liver cells are an ideal source for generating insulin-producing cells because they have regenerative ability and a developmental process similar to that of the pancreas. Pancreas versus liver fate is regulated by TALE homeoprotein (TGIF2) during development. Here, we wanted to investigate whether TGIF2 could enhance the efficiency of transdifferentiation of hepatocytes into insulin-producing cells induced by three pancreatic transcription factors (pTFs).The IVT mRNAs of TGIF2 and the 3 pTFs were synthesized in vitro and sequentially supplemented in hepatocytes. On day 6, the expression of transcription factors was assessed by quantitative qRT-PCR, and insulin expression was detected by immunofluorescence. Glucose-stimulated insulin secretion was assessed by enzyme-linked immunosorbent assay (ELISA). The key genes controlling cell polarity and the Wnt/PCP signaling pathway were assayed by qRT-PCR, and the level of JNK protein phosphorylation, which regulates the Wnt/PCP signaling pathway, was detected by western blotting.IVT mRNAs could be efficiently transfected into hepatocytes. qRT-PCR results revealed that compared with ectopic expression of the 3 pTFs alone, ectopic expression of the 3 pTFs plus TGIF2 could strongly reduce hepatic gene expression and subsequently improve the induction of a set of pancreatic genes. Immunofluorescence analysis showed that TGIF2 expression could double the transdifferentiation yield; 30% of the cells were insulin positive if induced by TGIF2 plus the 3 pTFs, while only 15% of the cells were insulin positive if induced by the 3 pTFs alone. ELISA analysis confirmed that glucose-stimulated insulin secretion was less efficient after transfection with the 3 pTFs alone. The differentiated cells derived from the addition of TGIF2 mRNA could form islet-like clusters. By contrast, the cells differentiated with the 3 pTFs did not form clusters under the same conditions. Overexpression of TGIF2 in hepatocytes could activate the expression of key genes controlling cell polarity and genes in the Wnt/PCP signaling pathway, increasing the level of JNK protein phosphorylation.Our study established a novel footprint-free protocol for efficient transdifferentiation of hepatocytes into insulin-producing cells using IVT mRNAs of TGIF2 and 3 pTFs,